Effect of fenofibrate on acute and subacute inflammation in male Wistar rats - Johny, Serah; S., Torgal S.; C., Ramesh; Mathew, Anna (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The objective of the study was to investigate the effect of fenofibrate on acute and subacute models of inflammation in adult male Wistar rats. Methods: After obtaining clearance from Institutional Animal Ethics Committee, six adult male Wistar rats were allocated to each of the three groups i.e. control, aspirin and fenofibrate. Acute inflammation was studied using carrageenan induced rat paw oedema and the volume displacement due to paw oedema was measured using the plethysmograph. Subacute inflammation was studied using foreign body insertion (cotton pellet and grass pith) models. Dry granuloma weight and histopathological examination of the granuloma were the outcome measures for measuring subacute inflammation. The percentage inhibition of inflammation with aspirin and fenofibrate was calculated in both acute and subacute models. The experiments were conducted according to the guidelines of the Committee for the Purpose of Control and Supervision on Experiments on Animals (CPCSEA). The mean volume displacement obtained with a plethysmograph, the mean dry weight of granuloma and the percentage inhibition with aspirin and fenofibrate were analyzed by one way analysis of variance (ANOVA) using Graph pad prism software. Results: Aspirin and fenofibrate significantly reduced both acute and subacute inflammation (p<0.001). Dunnet’s test showed a significant difference in the study groups when compared to the control. The reduction of inflammation with fenofibrate was comparable to aspirin. Conclusions: Oral fenofibrate showed significant anti-inflammatory activity, which was comparable to aspirin, in both acute as well as sub-acute models of inflammation. This anti-inflammatory effect may benefit atherosclerosis in patients receiving fenofibrate for hyperlipidemia.